John Gower, trilingual poet : language, translation, and tradition - Dutton, Elisabeth M.; Hines, John, 1956-; Yeager, Robert F. (Westfield medieval studies, 2010)
New essays demonstrate Gower's mastery of the three languages of medieval England, and provide a thorough exploration of the voices he used and the discourses in which he participated.